Coenzyme Q10 Deficiency and Migraine Response to Supplementation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The prevalence of coenzyme Q10 (CoQIO) deficiency and effectiveness of CoQIO supplements in treatment of migraine were assessed in a study at the Cincinnati Children's Hospital, OH.